Analisis Musik Musette In D Major Karya Johann Sebastian Bach - Febriyan, Tyo; Sudarman, Yos (SENDRATASIK UNP, 2019)
AbstractThis study aims to determine the musical structure of the Musette song in D Major by Johann Bach. This type of research was analysis content (content analysis) that displayed three conditions, namely: objectivity, systematic, and generalization. Objectivity was efforts to capture the nature (empirical) of an object that was being studied in a way that did not depend on any facilities from the subject that investigated it. The main instrument in this study was the researcher. Techniques of Data collection were carried out by taking literature study and observation. The steps in analyzing data were identifying the rhythm, melody and counter, as well as presenting data. The result of this study reveals the work of Musette in D Major by Johann Sebastian Bach that has a ternary part song form which is consisting of three periods. In each period, there are two phrases namely, the antecedent and the consequent phrases. In this work art, there is tonal counterparts element. Johann Sebastian Bach's Musette in D Major is a simple form of work art.Keywords: Musette In D Major, Analysis, Johann Sebastian Bach